2007
DOI: 10.1007/s11661-006-9055-8
|View full text |Cite|
|
Sign up to set email alerts
|

Orientation Relationship, Habit Plane, Twin Relationship, Interfacial Structure, and Plastic Deformation Resulting from the δ → α′ Isothermal Martensitic Transformation in Pu-Ga Alloys

Abstract: The orientation relationship, habit plane, parent-product interface at the atomic level, twin relationship, and plastic deformation resulting from the d fi a¢ isothermal martensitic transformation in Pu-Ga alloys are examined using optical microscopy, transmission electron microscopy (TEM), and finite element calculations. The d fi a¢ transformation exhibits ã 20 vol pct collapse when the fcc d phase transforms to the monoclinic a¢ phase, which results in unique and intriguing crystallography and morphology. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…In the case of thermal cycling, d M a 0 t causes plastic deformation in d and results in a high dislocation density. Transmission electron microscopy of similar thermally cycled material has shown that the dislocation density of samples heated at 300°C for 4 h is reduced 86 times in the highly damaged regions near the a 0 t plates [5]. Previous experiments on samples a Time required to transform during isothermal segment shown in parentheses.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of thermal cycling, d M a 0 t causes plastic deformation in d and results in a high dislocation density. Transmission electron microscopy of similar thermally cycled material has shown that the dislocation density of samples heated at 300°C for 4 h is reduced 86 times in the highly damaged regions near the a 0 t plates [5]. Previous experiments on samples a Time required to transform during isothermal segment shown in parentheses.…”
Section: Discussionmentioning
confidence: 99%
“…By integrating the endothermic peak of the DSC curves shown in Figure 1b to yield the area under each curve, the measured heat as a function of conditioning temperature can be obtained as plotted in Figure 2; the error bars are estimated to be ±100 mJ/g from the noise in the data and uncertainty in the subtracted baseline. The martensitic δ→α' transformation in Pu-2.0 at.% Ga is strain limited, resulting in an incomplete transformation yielding a maximum transformation of approximately 25% [9]. As such, the measured heat is proportional to both the thermodynamic heat of transformation (∆Η α ' →δ ) and the amount of α' transformed and thus subsequently reverted.…”
Section: Optimal Conditioningmentioning
confidence: 99%
“…Like all martensitic transformations, the d ! a 0 transformation in Pu-Ga alloys is diffusionless, is compositioninvariant, and produces a product phase (a 0 ) with a specific orientation relationship to the parent phase (d) [4,5]. Furthermore, this d !…”
Section: Introductionmentioning
confidence: 99%
“…a 0 transformation yields an a 0 phase that has a volume approximately 18% smaller than the d phase (V a 0 % 0:82V d ) [1,10]. This volume difference causes significant elastic and plastic strains in the vicinity of the transforming a 0 particle [5], and these strains likely limit the volumetric amount of a 0 product phase to about 25%. Thus, after undergoing the partial d !…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation